(untitled) (Estudos em Design, 2015)
The school is child’s experiences environment to participation in collective life. In it, the courtyard incorporates complexity and diversity of functions. In order to assess their physical conditions and relations with the appropriation of children, to adapt them to the specific requirements; the article presents a case study on Colégio de Aplicação of the Universidade Federal de Santa Catarina. The following were applied: observation, Architectural Survey and interviews, which resulted in spatial reading. The territoriality was essential to define the activities stations and to offer suggestions and recommendations.